2022
DOI: 10.3390/cells11081366
|View full text |Cite
|
Sign up to set email alerts
|

Tet1 Suppresses p21 to Ensure Proper Cell Cycle Progression in Embryonic Stem Cells

Abstract: Ten eleven translocation 1 (Tet1) is a DNA dioxygenase that promotes DNA demethylation by oxidizing 5-methylcytosine. It can also partner with chromatin-activating and repressive complexes to regulate gene expressions independent of its enzymatic activity. Tet1 is highly expressed in embryonic stem cells (ESCs) and regulates pluripotency and differentiation. However, its roles in ESC cell cycle progression and proliferation have not been investigated. Using a series of Tet1 catalytic mutant (Tet1m/m), knockout… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 36 publications
0
6
0
Order By: Relevance
“… 10 Individual deletion of Tet enzymes in ESCs does not impair self-renewal or pluripotency but compromises gene expression programs leading to aberrant differentiation in vitro. 8 , 9 , 11 , 12 , 13 Combined deficiency of all three Tets has more robust effects on the developmental potential of ESCs, suggesting some redundancy amongst Tet enzymes. 10 Consistently, mouse embryos lacking all three Tet enzymes cannot complete gastrulation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“… 10 Individual deletion of Tet enzymes in ESCs does not impair self-renewal or pluripotency but compromises gene expression programs leading to aberrant differentiation in vitro. 8 , 9 , 11 , 12 , 13 Combined deficiency of all three Tets has more robust effects on the developmental potential of ESCs, suggesting some redundancy amongst Tet enzymes. 10 Consistently, mouse embryos lacking all three Tet enzymes cannot complete gastrulation.…”
Section: Introductionmentioning
confidence: 99%
“… 6 We and others have shown that Tet1, independent of its catalytic activity, forms complexes with Sin3a and PRC2 to facilitate their recruitment to promoters of bivalent genes for H3K27 deacetylation and trimethylation. 11 , 12 , 17 , 18 Tet1-mediated recruitment of Sin3a has also been implicated in gene activation. 19 Tet2 interacts with several transcription factors and chromatin-modifying enzymes including O-liked N-acetylglucosamine transferase (Ogt), Klf4, Parp1, Hdac1/2, Nono, and Pspc1 in ESCs and other cell types.…”
Section: Introductionmentioning
confidence: 99%
“…Nicotinamide N-methyltransferase (NNMT) consumes methyl donors and makes SAM unavailable to other methyltransferases, thereby repressing H3K27me3 marks. NNMT is involved in the maintenance of the naïve state of ESC which are characterized by low levels of histone methylation ( 65 , 66 ).…”
Section: Intracellular Metabolic Pathways Implicated In the Regulatio...mentioning
confidence: 99%
“…Moreover, p21 transcription is suppressed in hESCs via H3K27 trimethylation of the p21 promoter, which is deposited by the EZH2 methyltransferase. Upon differentiation, the H3K27 trimethylation is rapidly lost and p21 expression is activated by p53 [ 61 , 62 ]. Interestingly, deletions of p21, p27, and p18 (another CDK inhibitor) enhance reprogramming efficiency [ 51 ].…”
Section: Cell Cycle Regulators Of G1 Progression In Stem Cells and Ca...mentioning
confidence: 99%